Conservative reporting, measurement similarity, and financial information comparability - Yu, Yao (2015)
This thesis examines whether the use of conservative versus aggressive accounting estimates (i.e., conservative/aggressive reporting) affects investors’ perception of financial information comparability (i.e., perceived comparability), and whether this effect is moderated by the extent to which firms use the same or different accounting measurements to record similar transactions (i.e. measurement similarity). Experiment 1 shows that conservative (as opposed to aggressive) reporting increases perceived comparability, and that this effect is significant only when firms use the same accounting measurement, not when firms use different accounting measurements. Experiment 2 finds a boundary condition for the results in Experiment 1; namely, a contrast between the conservatism/aggressiveness engaged in the firms’ reporting practices must be present so that investors can identify the different degrees of conservatism/aggressiveness in each firm’s reporting; otherwise, the effect of conservative/aggressive reporting on perceived comparability would disappear, including the moderating effect of measurement similarity. This thesis also examines investors’ investment decisions. Results from both experiments seem to indicate that investment decision is affected by two factors—perceived comparability and conservative/aggressive reporting. Specifically, perceived comparability increases investment in that more comparable information makes a firm’s superior financial performance more convincing. Meanwhile, conservative (as opposed to aggressive) reporting reduces investment probably because unsophisticated investors only take the “face value” of conservative reporting, instead of thinking that the underlying firm value should be higher than what is reported. Finally, this thesis finds that perceived comparability enhances investors’ confidence about their investment decisions and that this result is robust in both experiments.